The hidden costs of mental depression: implications on social trust and life satisfaction - Chee-Ruey, Hsieh; Siyuan, Liu; Xuezheng, Qin (University of Nottingham, 2017)
Mental health conditions such as depression is a rapidly rising epidemic and a major contributor to the overall global burden of disease. In addition to the direct medical costs and indirect economic costs that falls into the traditional boundary of disease burden estimation, many social costs associated with depression are hidden yet important. This paper provides empirical evidence on the existence of two hidden costs associated with depression: negative impact on social trust and life satisfaction. Based on the data obtained from 2012 China Family Panel Studies, our estimated results indicate that individuals who have a high tendency for depression or depressive symptoms are less likely to trust other people, and they also have significantly lower life satisfaction than their counterparts who are relatively mentally healthy. Given that trust is an important component of social capital, which in turn is an important input to foster economic growth in general and innovation in particular, the reduction in trust induced by the increasing prevalence of depression imposes a significant cost to the society in terms of poor economic performance. Similarly, as life satisfaction has been widely recognized as an important measure of well-being, our study also highlights that the increase in the prevalence of depression leads to a reduction in the well-being that individual can enjoy. All these costs are real, but did not receive sufficient attention in the previous research. The contribution of our research is to shed light on the existence of these hidden costs and to quantify the magnitude of such costs in the context of China.